Dampak ekspor, impor, dan nilai tukar petani terhadap pertumbuhan ekonomi di Jawa Tengah dengan indeks harga konsumen sebagai variabel moderasi - Lia Indriyani; Iskandar Iskandar (Journal of Economics Research and Policy Studies, 2025)
This study aims to examine the impact of Exports, Imports, and the Farmers' Exchange Rate on Economic Growth in Central Java Province during 2016-2023, with the Consumer Price Index (CPI) as a Moderating Variable. The method used in this study is a quantitative approach, using secondary data from the BPS publication website in the form of time-series data. The data used consist of monthly records from 2016 to 2023, totaling 96 observations. The data analysis method employed is multiple linear regression analysis with Moderated Regression Analysis (MRA). The results of this study indicate that exports, imports, and the Consumer Price Index have a positive and significant effect on economic growth. In contrast, the farmers' exchange rate has a positive but insignificant effect. Furthermore, the Consumer Price Index has been shown to moderate the negative impact of exports and imports on economic growth. However, it does not moderate the adverse effect of the farmers' exchange rate.